Implementasi Logika Fuzzy dalam Memprediksi Tingkat Kelulusan Tes Seleksi CPNS dengan Menggunakan Metode Tsukamoto - Romantika Tambunan; Murni Marbun (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
Applicants who take part in the selection of Candidates for Civil Servant Candidates (CPNS) must pass through the steps that must be taken which can determine the graduation rate. The criteria for predicting the passing of the CPNS selection test are used by the Basic Competency Selection (SKD) which consists of a Personal Characteristic Test (TKP), General Intelligence Test (TIU), National Insight Test (TWK), Competency Selection Section (SKB) which consists of a computer assisted test (CAT) and interviews, and the number of quotas received. This research is the implementation of Fuzzy Tsukamoto Logic in Predicting the Passing Rate of the CPNS Selection Test. The system for predicting the passing of the CPNS selection test was built using the Web-based PHP programming language. Data management using MySQL database. The overall defuzzyfication (Z) result in the system predicts the passing rate of CPNS = 61.950223979 = 62.